A low‐complexity iterative MIMO detection and decoding scheme using dimension reduction. Issue 1 (16th May 2014) - Shin, Sang‐Sik; Choi, Hongsoo; Jang, Jae‐Eun; Choi, Ji‐Woong
Abstract: Spatial multiplexing multiple‐input multiple‐output is considered as a core advanced communication technology to increase data rate. Although it guarantees higher capacity, it gives huge burden on the receiver side especially when iterative detection and decoding (IDD) is employed. Therefore, the IDD receiver needs to be efficiently implemented considering the complexity as well as performance in practice. In this paper, we propose an IDD scheme employing dimension reduction soft demodulation (DRSD) principle based on maximum a posteriori criterion necessary for IDD operation. With separation into hard and soft streams in the DRSD, the proposed scheme employs all ordering successive interference cancellation with a simple modified slicing for hard detection to consider the effect of a priori information conveyed from past iteration, enabling complexity reduction. It can provide better trade‐off between complexity and performance. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper proposed an iterative detection and decoding receiver that can be implemented with low complexity based on spatial stream separation into soft and hard streams when all ordering successive interference cancellation with the modified slicing is employed for hard detection while exhaustive search is used for soft streams. It can provide better trade‐off between complexity and performance.